Pharmaceutical Services Patient Needs Analysis in Out Patient Department RSUD dr. Soebandi Jember: Case Study Prescription Services - Olivia, Zora; Athijah, Umi; Utami, Wahyu (JURNAL ILMU KEFARMASIAN INDONESIA, 2019)
The aim of this research was to know the drug related need in the pharmacy service at pharmacy special prescription service. Descriptive study was done to out patient who fulfi ll prescription in the pharmacy Dr Soebandi Jember Hospital. A sample of this population is 557 patients taken with sampling techniques with stratifi ed random sampling. Retrieval of data in this study using a questionnaire instrument. From the data needs of the patient at the pharmacy pharmacy services in the majority of patients explain need to therapy appropriate treatment indication for 85.6 %, at eff ective 84.9 %, at safely 77.4 % and can be used according to the rules of use of 94.4 %. Based on these data it can be concluded that the needs of patients at the pharmacy services are appropriate indications, eff ective, safe and can be used according to the rules of use. The requirement can be achieved due to appropriate pharmacy services running and providing pharmaceutical care is a pharmacist. Reimbursements are reimbursed by the insurance company should not be given to Pharmacist Pharmacy for pharmaceutical care can not walk if no pharmacist.